Credit risk transfer and bank insolvency risk - Maarten R. C. van Oordt (Bank of Canada, 2017)
The present paper shows that, everything else equal, some transactions to transfer portfolio credit risk to third-party investors increase the insolvency risk of banks. This is particularly likely if a bank sells the senior tranche and retains a sufficiently large firstloss position. The results do not rely on banks increasing leverage after the risk transfer, nor on banks taking on new risks, although these could aggravate the effect. High leverage and concentrated business models increase the vulnerability to the mechanism. These results are useful for risk managers and banking regulation. The literature on credit risk transfers and information asymmetries generally tends to advocate the retention of 'information-sensitive' first-loss positions. The present study shows that, under certain conditions, such an approach may harm financial stability, and thus calls for further reflection on the structure of securitization transactions and portfolio insurance.
Keywords: G21; G28; G32; 330; Credit risk management; Financial institutions; Financial stability